An Analysis of Code-Switching Used by the Models and Judges in Indonesia's Next Top Model Cycle 2 - Rebecca Paramitha Utami; Ruswan Dallyono (Passage, 2022)
This study entitled “An analysis of code-switching used by the models and judges in Indonesia’s Next Top Model Cycle 2” aims to analyze the types and factors of code-switching that were found in the TV show. This study used a descriptive qualitative method in which the data were obtained from the video downloaded from YouTube. The data were in the form of utterances of all the models and judges in the TV show. Drawing on Appel and Muysken’s (2006) types of code switching and Hoffman’s (1991) factors contributing to code switching, the results of the study revealed that there were 167 types and 172 factors of code-switching in Indonesia’s Next Top Model Cycle 2: 13.17% (22) inter-sentential switching, 78.44% (131) intra-sentential switching, 6.59% (11) tag-switching, and 1.80% (3) inter-sentential switching in Bahasa Indonesia-Javanese. Meanwhile, the factors that found were talking about particular topic, being emphatic about something, interjection, repetition, intention to clarify, and expressing group identity. The most dominant factors were talking about particular topic 64.53% or 111 data and followed by intention of clarifying the speech content for interlocutors 14.53% or 25 data. The findings of the study indicated that intra-sentential switching was used dominantly to assure the audience of the show, which is mostly Indonesians, can understand entirely the conversation. Additionally, the subjects used code-switching to talk about particular topic, mostly for fashion terminologies, as it is intended to create an exclusivity for the people who belong to the same group, which is fashion enthusiasts.